Aplikasi Deep Eutectic Solvents (DESs) Sebagai Katalis Pada Sintesis Emulsifier - Laisa Husraini; Ida Zahrina; Sunarno Sunarno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Monoglycerides (MG) and diglycerides (DG) are a group of synthetic emulsifiers that can be obtained from the process of esterification of fatty acids with glycerol using several types of acid-based catalysts, such as ZnO, zinc carboxylate, ZnCl2 and MgO. Recently, deep eutectic solvents (DESs) is used in the process of esterification replacing acid-based catalysts. DES is a system that consists of a mixture of at least two components: hydrogen bond acceptors (HBA) and hydrogen bond donors (HBD) which form eutectic phases that melting points are lower than the constituent components. DES application in the esterification process for the purpose of food grade takes into account the level of toxicity so that DES is made from the composition of green chemistry compounds known as NADES (Natural Deep Eutectic Solvents). NADES is a non-toxic DES group so that it can be applied in processing emulsifier raw materials as additives for food products. In addition, DES can be used repeatedly (reused catalyst) and the results show that the catalyst activity is well. The use of DES which acts as a catalyst and reused catalyst can save costs without reduced the conversion. Key words: DES, emulsifier, esterification, reused catalyst